The Role of Artificial Intelligence in Endoscopic Ultrasound for Pancreatic Diseases - Ancuța Năstac; Alexandru Constantinescu; Octavian Andronic; Dan Nicolae Păduraru; Alexandra Bolocan; Bogdan Silviu Ungureanu (Gastroenterology Insights)
The integration of artificial intelligence (AI) into healthcare, particularly in the field of gastroenterology, marks a significant advancement in the diagnosis and treatment of pancreatic disorders. This narrative review explores the application of AI in enhancing Endoscopic Ultrasound (EUS) imaging techniques for pancreatic pathologies, focusing on developments over the past decade. Through a comprehensive literature search across several scientific databases, including PubMed, Google Scholar, and Web of Science, this paper selects and analyzes 50 studies that highlight the role, benefits, precision rates, and limitations of AI in EUS. The findings suggest that AI not only improves the quality of endoscopic procedures, as acknowledged by a majority of gastroenterologists in the UK and USA, but also offers a promising future for medical diagnostics and treatment, potentially addressing the shortage of specialists and reducing morbidity and mortality rates. Despite AI’s infancy in clinical applications and the ethical concerns regarding data privacy, its integration into EUS has enhanced diagnostic accuracy and provided minimally invasive therapeutic alternatives. This review underscores the necessity for further clinical data to evaluate the applicability and reliability of AI in healthcare, advocating for a collaborative approach between physicians and AI technologies to revolutionize the traditional clinical diagnosis and expand treatment possibilities in gastroenterology.